Study on basic material properties of artificial snow - Lintzén, Nina; Edeskär, Tommy (Luleå tekniska universitet, Geoteknologi, 2012)
For buildings and constructions made by snow, like for example the ICEHOTEL in Jukkasjärvi, generally artificial snow is used. Both for safety reasons and for design purposes it is hence of importance to understand the material behaviour of artificial snow. Many buildings and structures made by snow and ice are constructed using knowledge obtained by experience.When subjected to a load snow undergoes an immediate elastic deformation and a time-dependent irreversible deformation, known as snow creep, which constitutes the considerably highest part of the total deformation. The magnitude of the snow creep deformation is the dominating deformation mechanism for snow structures but it is poorly investigated and not well understood.To study material parameters and mechanical behaviour of artificial snow unconfined compression test and deformation tests to observe the creep behaviour have been performed. Results from experimental tests have been analyzed and compared with theoretical calculations and finite element simulations. The density and viscosity have shown to be important parameters for the deformation behaviour and will have a direct influence on the creep rate. The investigation indicates that the artificial snow used for the tests have higher density, compression strength and creep strength compared to natural snow used in other studies. Validerad; 2012; 20120607 (ysko)